Kajian Rancangan Promo Album Faito 61 Tahun 2008 - I Nyoman Anom Fajaraditya Setiawan (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2017)
Music has many lovers, especially in Bali there are many bands from various musical genres. In the development of indie music labels required hard work in creativity as supporting the popularity and success in the field of music. Faito 61, the band that existed from many hardcore bands of Bali maintained its existence with it so it is known among hardcore music fans from 2004-2010. Efforts to improve creativity and quality, Faito 61 released its first album as proof of maturity to fans and the community in addition to the creations of musicians that can generate and increase the band's popularity. It utilizes visual communication media as a supporting tool to maximize the album promo and this can also increase the popularity and sales of Faito 61 album. The existing media is so diverse that it needs to be selective and in accordance with theories, concepts and field conditions. For such provision it must begin with research and theoretical review. The hardcore concept is lifted according to the flow of the band. The design of Faito 61 album promo media, applied hardcore elements ranging from illustrations, typography and colors. Data obtained from direct interviews with direct observation media that has been owned so far then compared with design theory. Further analyzed qualitatively so that it can be concluded as the basic design.